Investigation of the Structural, Thermal, and Physicochemical Properties of Nanocelluloses Extracted From Bamboo Shoot Processing Byproducts - Lin, Tong; Wang, Qi; Zheng, Xuan; Chang, Yu; Cao, Hui; Zheng, Yafeng (Frontiers in Chemistry, 2022)
Nanocellulose has gained increasing interests due to its excellent properties and great potential as a functional component in food industry. This study investigated the structural, thermal and physicochemical properties of nanofibrillated cellulose (NFC) and nanocrystalline cellulose (CNC) extracted from bamboo shoot (Leleba oldhami Nakal) processing byproducts. NFCs were prepared through low concentration acid hydrolysis combined with ultrasonic treatment. CNCs were further isolated from NFCs using sulfuric acid hydrolysis treatment. TEM images showed that NFC and CNC exhibited typical long chain and needle-like structure, respectively. CNC suspension was stable due to its zeta potential of -34.3 mV. As expected, both NFC and CNC displayed high crystallinity indexes of 68.51% and 78.87%, and FTIR analysis confirmed the successful removal of lignin and hemicellulose during the treatments. However, thermogravimetric analysis indicated that sulfuric acid hydrolysis decreased the thermal stability of CNCs. The improved physicochemical properties of NFC and CNC suggested their potential in various applications.